Analisis Pengaruh Indikator Ekonomi Makro Terhadap Pendapatan Asli Daerah Provinsi Kepulauan Bangka Belitung Pada Tahun 2012-2021 - Agung Rizki Putra; Novita Herlissha; M. Afdal Samsuddin; Tiara Fitari; Indah Noviyanti (Economics and Digital Business Review, 2023)
PAD is income earned by the Region which is collected based on Regional Regulations in accordance with statutory regulations. This regional original income can be used as the main capital in administering government and development. The level of PAD in Bangka Belitung has fluctuated over the last six years. The aim of this study was to analyze the effect of macroeconomic indicators on local revenue of the Bangka Belitung Islands Province (2012-2021). The macroeconomic indicators in this study are regional gross domestic product (GDP), population, and inflation over a 10-year period, from 2012 to 2021. This study uses multiple linear regression analysis to see the effect between GRDP, total population, and inflation against regional original income. The results of the regression analysis stated that GRDP had a significant positive effect on local own-source income, in addition to that the population also had an effect on regional original income, but the effect was significant negative. Meanwhile, the regression results do not show that inflation has a significant effect on local revenue in the Bangka Belitung Islands Province.